Model Pengadaan Obat dengan Metode ABC VEN Di RS X Semarang - Siska Wulandari; Sugiarto Sugiarto (Jurnal Manajemen Kesehatan Indonesia, 2019)
Procurement of drugs at RS X was carried out unsystematically by the head of the RS Pharmacy Installation. This procurement causes the costs incurred by the Hospital to be unplanned and inefficient. The value of the use of active pharmaceutical supplies in 2016 with the number of pharmaceutical supplies of 2119 is worth Rp. 168,232,696 and the number of 2041 inactive supplies worth Rp. 533,260,268. The data shows the inefficiency of pharmaceutical supplies within 1 year which results in the use of budget funds less efficiently. The purpose of this study was to determine the role of the ABC VEN method as a basis for procurement systems in Hospital X.       The type of research conducted is quantitative, pre experimental using descriptive analytical methods with analysis of ABC and VEN methods. Samples were taken as much as 500 from the data of drug use for 1 year in RS X Pharmacy Installation.       The results of the study of 500 drug items with the ABC method found Group A 19.8%, Group B 40%, Group C 40.2%, the VEN method obtained group V 7.8%, Group E 88.8%, group N 3, 4%, with the ABC method VEN AV group 2%, AE 17.6%, AN 0.3%, BV 4.2%, BE 35%, BN 1.2%, CV 1.8%, CE 37%, CN 1.8%. The CE (C Essential) group is more due to its function as prevention and prevention of patient diseases. Before doing the ABC VEN method the inventory value is Rp. 6,188,183,555 and after the ABC VEN method was Rp. 5.833.095.547 with a difference of Rp. 355.089.998, (6.8%) of the total usage fee.        The conclusion of this study is that the system used by the Pharmacy Pharmacy Installation has not been efficient, causing losses for hospitals. Difference in inventory value before and after the ABC VEN method is Rp. 355,089,998. Suggestions are changing the old system to a new system through prior socialization and regulation.